URGENSI PENGETAHUAN PARENTING SKILL ISLAMI BAGI ORANG TUA UNTUK PEMBINAAN AKHLAK ANAK - Fadhlika Cahya Ningrum (IAIN Ponorogo, 2021)
Morals are one of the important things in everyday human life. Having good morals will be accompanied by good teaching and learning activities as well. Parents have a big enough share and are very important for the formation of children's character/personality, especially when they are still at an early age. The knowledge of parenting skills is not only obtained or learned from one party, but from both parties (Father and Mother) must agree on values that can help or hone these parenting skills for parents. The things or values that can be passed down to children are: (1) be a good role model for children, (2) always be calm, (3) always explain the consequences of good and bad behavior in children, (4) encourage children to build self-esteem, (5) Say and show the unconditional love of parents to children.